2012
DOI: 10.1177/0885728811432165
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Beyond High School Model on the Self- Determination of Students With Intellectual Disability

Abstract: Students with intellectual disability are often served in community-based services to promote effective adult outcomes in employment, community inclusion, and independent living (Gaumer, Morningstar & Clark (2004). Beyond High School (Wehmeyer, Garner, Lawrence, Yeager, & Davis, 2006), a multi-stage model to promote student involvement in educational planning, was effectively used by 109 students with mild and moderate levels of intellectual disability between 17.8 and 21 years of age to increase student abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Eurther, data exists to support the efficacy of several studentinvolvement in educational planning interventions as having a positive effect on self-determination and student involvement (Martin et al, 2006;Palmer et al, 2012;Wehmeyer, Palmer, Lee, Williams-Diehm, & Shogren, 2011). Many of these studies involve single-case design or quasiexperimental studies, though several more recent ©AAIDD DOI: 10.1352DOI: 10.…”
Section: Research Provides Efficacy Evidence For Interventions To Promentioning
confidence: 93%
“…Eurther, data exists to support the efficacy of several studentinvolvement in educational planning interventions as having a positive effect on self-determination and student involvement (Martin et al, 2006;Palmer et al, 2012;Wehmeyer, Palmer, Lee, Williams-Diehm, & Shogren, 2011). Many of these studies involve single-case design or quasiexperimental studies, though several more recent ©AAIDD DOI: 10.1352DOI: 10.…”
Section: Research Provides Efficacy Evidence For Interventions To Promentioning
confidence: 93%
“…This is accomplished using the strategies and questions comprising the third phase of the SDLMI . Palmer, Wehmeyer, Shogren, WilliamsDiehm, and Soukup ( 2012 ) conducted a randomized control trial study of the BHS process with 109 students with intellectual disability enrolled in post-secondary education, fi nding that students involved with the BHS process had more positive self-determination related outcomes than their peers in the control group.…”
Section: Self-determined Learning Model Of Instructionmentioning
confidence: 99%
“…In distinct meta-analyses of single-subject and group-subject design studies, Algozzine, Browder, Karvonen, Test, and Wood (2001) found evidence for the efficacy of instruction to promote component elements of self-determined behavior, including interventions to promote self-advocacy, goal setting and attainment, self-awareness, problemsolving skills, and decision-making skills. Also, research documents the positive impact of efforts to promote student involvement in educational and transition planning (Martin et al, 2006;Palmer, Wehmeyer, Shogren, Williams-Diehm, & Soukup, 2012;Test et al, 2004) on more positive transition and self-determination related outcomes, particularly employment, community inclusion, and independent living. Cobb, Lehmann, Newman-Gonchar, and Alwell (2009) conducted a narrative metasynthesis (a narrative synthesis of multiple meta-analytic studies) covering seven existing meta-analyses examining self-determination and concluded that there is sufficient evidence to support the promotion of self-determination as effective.…”
Section: Importance Of Self-determination To Youth With Disabilitiesmentioning
confidence: 99%
“…Students in the treatment group showed higher levels of self-determination (effect sizes d < .70 and .73), as well as reporting higher quality of life and utilization of community transition services. Also, research documents the positive impact of efforts to promote student involvement in educational and transition planning (Martin et al, 2006;Palmer, Wehmeyer, Shogren, Williams-Diehm, & Soukup, 2012;Test et al, 2004) on more positive transition and self-determination related outcomes, particularly employment, community inclusion, and independent living.…”
Section: Importance Of Self-determination To Youth With Disabilitiesmentioning
confidence: 99%